Impact of an empathy-based mental health first aid intervention using the SUFA model on anxiety and depression among adolescents: a quasi-experimental study - Sulastri Sulastri; Siti Fatonah; Yuniastini Yuniastini; Giri Udani; Allan Harris (Intelektual Pustaka Media Utama, 2026)
This study evaluated the effectiveness of an empathy-based mental health first aid (MHFA) intervention through structured SUFA mentoring by peer counselors in reducing symptoms of anxiety and depression in adolescents. The design used was a quasi-experimental, one-group pretest-posttest study conducted over two weeks in middle and high schools. A total of 100 students were trained as peer counselors, and each mentored one adolescent (a 1:1 ratio). Symptoms were measured before and after the intervention using the Mini MINDHEAR Youth Scale V.1. Analysis included descriptive statistics (mean pre–post scores and changes in symptom categories of